Distal Macro- and Microembolization During Subintimal Recanalization of Femoropopliteal Chronic Total Occlusions. (August 2014) - Spiliopoulos, Stavros; Theodosiadou, Vasiliki; Koukounas, Vasilios; Katsanos, Konstantinos; Diamantopoulos, Athanasios; Kitrou, Panagiotis; Ravazoula, Panagiota; Siablis, Dimitris; Karnabatidis, Dimitris
Purpose: To investigate the phenomenon of distal embolization during subintimal angioplasty with or without stenting of femoropopliteal chronic total occlusions (CTOs). Methods: This prospective study included 40 consecutive patients (35 men; mean age 65.4±9.3 years) who underwent subintimal angioplasty alone (n=14) or with stenting (n=26) of CTOs in the femoropopliteal segment. A Spider protection filter was used to capture any possible macro- or microemboli generated during balloon inflation/stenting. Arterial outflow was angiographically checked during each consecutive procedural step. All filters were examined on site for macroscopic material, while the first 20 filters underwent further histopathological qualitative and semiquantitative analysis using a 0+ to 3+ score. Results: There was no angiographically or clinically evident distal embolization. Macroscopic particulate debris was not detected in any filter. Histopathology confirmed the absence of macroemboli but revealed microembolic material (diameter <100 μm) in all filters (20/20). The mean number of particles detected was 9.4±4.5 (range 5-17). Histopathological findings included fibrin conglomerates (20/20), trapped erythrocytes (19/20), inflammatory cells (16/20), calcification minerals (6/20), extracellular matrix (6/20), cholesterol clefts (6/20), and endothelial cells (6/20). Captured material was classified as fresh and old thrombus in 7/20 and 4/20 cases, respectively. Semiquantitative analysis demonstrated that the collected microparticles consisted primarily of fibrin conglomerates (median score 2+), trapped erythrocytes (median score 1+), and inflammatory cells (median score 1+). Conclusion: Macroscopically evident emboli were not detected following subintimal angioplasty or stenting of femoropopliteal CTOs. Microscopic debris was present in all filters. The clinical significance of the phenomenon remains to be determined.